2019
DOI: 10.1136/bmjopen-2019-031170
|View full text |Cite
|
Sign up to set email alerts
|

Changes in quality of life 5 years after sleeve gastrectomy: a prospective cohort study

Abstract: ObjectivesSleeve gastrectomy (SG) is the most frequently performed bariatric surgery procedure worldwide, but reports on long-term quality of life (QOL) outcomes are scarce. We investigated 5-year trajectories in QOL and their associations with weight loss after SG.DesignA prospective cohort study.SettingThe study was conducted in a single Norwegian bariatric surgery centre.ParticipantsOut of 150 operated patients, 127 were included. Mean age was 41 years, 68% were women and the follow-up rate at 1 year was 85… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 49 publications
2
19
0
2
Order By: Relevance
“…QOL assessed at three different levels showed considerable improvements at 1–2 years and a gradual decline thereafter yielding bi-phasic patterns of parallel changes in BMI and QOL, as previously reported in RCTs and in our observational study after SG [ 13 , 21 , 38 ]. To our knowledge, a comprehensive assessment of QOL at different levels has not been done in other comparative trials of bariatric procedures.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…QOL assessed at three different levels showed considerable improvements at 1–2 years and a gradual decline thereafter yielding bi-phasic patterns of parallel changes in BMI and QOL, as previously reported in RCTs and in our observational study after SG [ 13 , 21 , 38 ]. To our knowledge, a comprehensive assessment of QOL at different levels has not been done in other comparative trials of bariatric procedures.…”
Section: Discussionsupporting
confidence: 83%
“…We therefore prospectively compared long-term outcomes after surgery in patients with severe obesity in a real-world clinical setting in Western Norway. To better capture the impact of bariatric surgery on patients’ QOL, we differentiated between narrow QOL concepts associated with changes of body weight, and broader aspects of QOL employing obesity-specific-, generic health-related and overall QOL questionnaires [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of bariatric surgery have used more comprehensive patient reported outcome measures (PROMs). Weight loss after bariatric surgery is strongly associated with improvement in QoL [ 22 , 23 ]. However several other studies have found a negative association between GI symptoms and QoL [ 9 , 10 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Self-rated health (SRH) is a good predictor of morbidity, mortality, and healthcare use [ 18 ], and chronic pain is independently associated with SRH [ 19 ]. Most patients experience improvement of quality of life (QoL) after RYGBP or LSG surgery [ 20 , 21 ], often related to WL [ 22 , 23 ] but also to reduced prevalence and intensity of GI symptoms and abdominal pain [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a disease not only through the risk of associated comorbidities but it is also cause of daily difficulties, leading to a decrease in QoL. Surgical treatment of obesity in addition to improving the QoL offers the individual a social, family, emotional and psychological reintegration [ 23 , 24 ]. Changes in self-image and self-esteem after bariatric surgery have a positive influence on QoL [ 25 ].…”
Section: Discussionmentioning
confidence: 99%